2006
DOI: 10.1021/bc060010a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Functionalized Biotin N-1‘ Derivatives:  New Tools for the Control of Gene Expression with Small Molecules

Abstract: The exceptionally high affinity of biotin toward avidin and streptavidin is at the basis of (strept)avidin-biotin biotechnology, which has numerous applications in life sciences. Recent biotin developments for in vivo and in vitro acylation of selective targeted protein and intein-mediated site specific protein biotinylation require the free biotin carboxyl function to covalently bind with the targeted protein. However, recently this carboxylic function has been used to substitute biotin with numerous ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Trimer 3 was N-Boc deprotected with TFA and evaporated to produce the crude TFA salt that was subsequently extended by D-Biotin through EDC-HCl mediated coupling to form the biotinylated trimer linker 4 scaffold in 80% yield. Inard et al 16 demonstrated that sulfur containing biotin derivatives were inert towards palladium, and thus palladium-mediated hydrogenation of benzyl ester 4 liberated the free carboxylic acid of the biotinylated linker 5 in 84% yield. Biotinylated linker 5 was equipped for direct esterification with the appropriate bioactive molecule, such as lagunamide A.…”
Section: Resultsmentioning
confidence: 99%
“…Trimer 3 was N-Boc deprotected with TFA and evaporated to produce the crude TFA salt that was subsequently extended by D-Biotin through EDC-HCl mediated coupling to form the biotinylated trimer linker 4 scaffold in 80% yield. Inard et al 16 demonstrated that sulfur containing biotin derivatives were inert towards palladium, and thus palladium-mediated hydrogenation of benzyl ester 4 liberated the free carboxylic acid of the biotinylated linker 5 in 84% yield. Biotinylated linker 5 was equipped for direct esterification with the appropriate bioactive molecule, such as lagunamide A.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing concentrations of NaCl were used to elute the labeled scFv, which was obtained at NaCl concentrations of 400 to 600 mM (Figure 3). We have shown that N′1 modifications of D-biotin result in a major loss of affinity for avidin (35). We made use of this property in the purification of labeled scFv on streptavidin, by adding biotin to the elution buffer.…”
Section: Discussionmentioning
confidence: 99%
“…It was essential for this labeling to be selective and to have no effect on antigen-scFv recognition. On the basis of previous work on the synthesis of functionalized biotin N-1′ derivatives (35), we synthesized a biotin N-1′ fluorescein derivative carrying a thiol inducer of intein splicing on its valeric chain. This molecule double-labeled the scFv, its biotin moiety facilitating purification of the labeled protein and its fluorescein moiety opening up opportunities for the use of fluorescence-based technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 However, when compound 133 was allowed to react with CSA, ether 134 again was obtained as the major product as indicated by TLC. 120 When this mixture proved difficult to separate, the mixture was treated with TsOH in MeOH in hopes that the two compounds could be separated following deprotection of the MOM-acetal. However, this also produced an inseparable mixture of the two products.…”
Section: Figure 40 Attempted Alkylation Of Benzyl Alcohol 104mentioning
confidence: 99%